Does it Make Sense to Store Fresh Roots? - Stathers, T.; Tedesco, I. (International Potato Center, 2015)
This flyer is a brief description of a study undertaken to better understand whether fresh root storage might offer opportunities with the Kenyan OFSP supply chain. 59 stakeholder and focus group interviews were undertaken across eight focal counties in Kenya to understand existing sweetpotato value chains, their seasonality, farmers’ production trends and constraints, traders’ root sourcing and trading patterns, price dynamics, retailing behaviors and consumers’ preferences.